2014
DOI: 10.2320/matertrans.m2014036
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pre-Strain on the Resistance to Hydrogen Embrittlement in 316L Austenitic Stainless Steel

Abstract: The effect of pre-strain before hydrogen charging on the resistance to hydrogen embrittlement (HE) in the 316L austenitic stainless steel was investigated through the slow strain rate tensile test (SSRT), transmission electron microscopy, and thermal desorption analysis (TDA). The pre-strain suppressed mechanical twinning during the SSRT, regardless of hydrogen charging. However, it accelerated the ¾-martensitic transformation in hydrogen-charged specimens. The TDA revealed that whereas hydrogen atoms migrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…2a). Instead, the 2nd peak, which is known to be generated by hydrogen atoms detrapped from twin boundaries [16,28], newly appeared at temperatures ranging between approximately 500 K and 600 K. This result implies that hydrogen atoms were transported from grain boundaries, dislocations, and lattices (the 1st peak) to twin boundaries (the 2nd peak) during the SSRTs, which shows good agreement with previous results obtained using other TWIP steels [16,31] and austenitic stainless steels [28,29]. The height of the 2nd peak increased with increasing grain size, implying that the migration of hydrogen atoms was more active in coarse-grained specimens most likely due to the high volume fraction of mechanical twins.…”
Section: Variations In Tensile Properties As Functions Of Grain Size supporting
confidence: 90%
See 3 more Smart Citations
“…2a). Instead, the 2nd peak, which is known to be generated by hydrogen atoms detrapped from twin boundaries [16,28], newly appeared at temperatures ranging between approximately 500 K and 600 K. This result implies that hydrogen atoms were transported from grain boundaries, dislocations, and lattices (the 1st peak) to twin boundaries (the 2nd peak) during the SSRTs, which shows good agreement with previous results obtained using other TWIP steels [16,31] and austenitic stainless steels [28,29]. The height of the 2nd peak increased with increasing grain size, implying that the migration of hydrogen atoms was more active in coarse-grained specimens most likely due to the high volume fraction of mechanical twins.…”
Section: Variations In Tensile Properties As Functions Of Grain Size supporting
confidence: 90%
“…The hydrogen desorption rate was measured by TDA before and after the SSRTs during continuous heating at a constant rate of 100 K h À1 from room temperature to 650 K. The hydrogen desorption rate was normalized to the surface area of each sample. Each peak on the hydrogen desorption rate curve was converted to a hydrogen concentration [11,18,29,31].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the migration of hydrogen atoms toward the interfaces of Ti particles instead of twin boundaries implies that hydrogen atoms eventually migrate to trapping sites with a stronger binding energy with themselves. Recently, the migration of hydrogen between different trapping sites during the SSRT has been investigated by observing the changes in hydrogen desorption peaks [44,45]. It is reported that hydrogen migrates to the stronger trapping site through mobile dislocations during deformation [32,35].…”
Section: Hydrogen Migration During the Ssrtmentioning
confidence: 99%